(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the current pattern and outcome of the closed diaphyseal humeral fracture treated with intramedullary interlocking nail. Study Design: Descriptive study Place and Duration of Study: This study was carried out at Orthopedic Department of Liaquat University Hospital Hyderabad and PUMHS Benazirabad Nawabshah from March 2011 to February 2012. Materials and methods: All the 40 patients with closed diaphyseal humeral shaft fracture between the ages 15-45 years were included in the study. All the patients after counseling and diagnosed as case with closed diaphyseal humeral shaft fracture on the basis of clinical examination and X-rays. Closed intramedullary nailing management procedure was used for closed diaphyseal humeral shaft fracture regarding with clinical presentation, preoperative findings and functional outcomes were documented including postoperative complications. Results: Total 40 patients were selected in this study with humeral fracture. Male were found in majority. From types of fractures transverse fractures were most common 45% and road accidents were seen in majority. Most common complication was post operative pain in 40% of cases; Excellent results were found in the 55% of the cases while good in 20%, fair in 10% and 5% results were noted poor in the patients Conclusion: In the conclusion of this study the closed intramedullary interlocking nailing procedure is the very good method for treatment of fracture shaft of humerus including with very good outcome.